Mr. Dymoke, The King's Champion. (From An Authentic History Of The Coronation Of His Maiesty King George The Fourth By Robert Huish, Esq. 1821.) (Tufts Archival Research Center, 2005)
This illustration is from Walter Thornbury "Old and new London, a narrative of its history, its people, and its places, vol. 3"